Hematology scoring model to predict sepsis in preterm neonates - Suryani, Yani Dewi; Yuniati, Tetty; Kadi, Fiva Aprilia; Primadi, Aris (Indonesian Pediatric Society, 2024)
Background Neonatal sepsis is a major cause of neonatal morbidity and mortality, especially in developing countries. Atypical clinical symptoms lead to delays in diagnosis and treatment. Scoring a combination of routine hematology parameters may be able to predict the occurrence of sepsis in preterm neonates. Objective To formulate a new model for neonatal sepsis scoring from various complete blood count parameters to predict sepsis in preterm neonates. Methods This analytical cross sectional study using secondary data from the Registry of the Neonatology Division was conducted at the RSUP Dr. Hasan Sadikin, Bandung, West Java. Subjects were neonates diagnosed with sepsis, of gestational age 28–36 weeks, who were born at the RSUP Dr. Hasan Sadikin from January to December 2021. Laboratory results of patients who met the inclusion criteria were recorded. Subjects were divided into either proven sepsis and probable sepsis groups, based on blood culture results. Results Of 112 subjects, 35.7% had proven sepsis and 64.3% probable sepsis. In the proven sepsis group, 52.5% of subjects were male, median birth weight was 1,490 grams, median gestational age was 32 weeks, 90% were small for gestational age, and 60% were delivered normally. Multivariable analysis by multiple logistic regression revealed that the parameters associated with the incidence of neonatal sepsis were c-reactive protein (CRP) > 0.18 mg/dL (score 6), hematocrit <40% (score 4), platelet-to-lymphocyte ratio (PLR) < 19.623 (score 4); monocyte-lymphocyte ratio (MLR) < 0.461 (score 2); and mean platelet volume (MPV) value >10 (score 2). Score >8 had a sensitivity of 85% and specificity of 70.8%, with area under the ROC curve of 0.865 (P<0.001). Scoring accuracy was 75.8%, with a positive predictive value of 61.8%, a negative predictive value of 89.5%, and Kappa index of 51.5% with moderate agreement. Conclusion A hematological score >8 can be used as a predictor of sepsis in preterm neonates.